Alterations in structural macromolecules and chondrocyte deformations in lapine retropatellar cartilage 9 weeks after anterior cruciate ligament transection. Issue 1 (31st July 2017) - Han, Sang‐Kuy; Ronkainen, Ari P.; Saarakkala, Simo; Rieppo, Lassi; Herzog, Walter; Korhonen, Rami K
ABSTRACT: The structural integrity and mechanical environment of the articular cartilage matrix directly affect chondrocyte deformations. Rabbit models of early osteoarthritis at 9 weeks following anterior cruciate ligament transection (ACLT) have been shown to alter the deformation behavior of superficial zone chondrocytes in mechanically loaded articular cartilage. However, it is not fully understood whether these changes in cell mechanics are caused by changes in structural macromolecules in the extracellular matrix. Therefore, the purpose of this study was to characterize the proteoglycan content, collagen content, and collagen orientation at 9 weeks post ACLT using microscopic techniques, and relate these changes to the altered cell mechanics observed upon mechanical loading of cartilage. At 9 weeks following ACLT, collagen orientation was significantly ( p < 0.05) altered and proteoglycan content was significantly ( p < 0.05) reduced in the superficial zone cartilage matrix. These structural changes either in the extracellular or pericellular matrix (ECM and PCM) were also correlated significantly ( p < 0.05) with chondrocyte width and height changes, thereby suggesting that chondrocyte deformation response to mechanical compression in early OA changes primarily because of alterations in matrix structure. However, compared to the normal group, proteoglycan content in the PCM from the ACLT group decreased less than that in the surrounding ECM. Therefore, PCM could play a key role to protect excessive chondrocyte deformations in the ACLT group. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:342–350, 2018. Abstract : The PG content in the superficial zone PCM decreased in the ACLT group compared to the normal group samples. However, this PCM PG loss was not as extensive as that in the surrounding ECM, which can be observed from the significantly higher PCM to ECM PG content ratio in the ACLT group compared to the normal or C‐L group samples (Figure shown as normalized PCM to ECM PG content).